Upaya Penegakkan Hukum Dibidang Hak Kekayaan Intelektual - Azed, Abdul Bari (Pelita Harapan University, 2005)
As one of developing countries Indonesia, faced with the challenge of globalization, Â has taken the necessary measures to reform its laws especially those that are in connection with the protection of intellectual property rights. The policy that has been taken up to the present time is to adjust, that is to adopt and incorporate, laws concerning the regulation of free market and the free movement of goods and services in the coming single global market system. The urgency of making such policy is to assure an adequate legal protection for the creator, inventor and designer of the intellectually created Â goods or services. With that kind of appreciation it is hoped that, in turn, that will bring economic benefit and advantage to the nation. There are series of laws and regulations being adopted from international instruments as well as national laws. The article deals mainly with the legal analysis of the impact of making the current legal policy.